Testing the validity and reliability of the Matching Familiar Figures Test-2021: An updated behavioral measure of reflection–impulsivity - Viator, Ralph E.; Wu, Yi-Jing; Viator, Allison S. (Frontiers in Psychology, 2022)
The Matching Familiar Figures Test (MFFT) is a well-known and extensively used behavioral measure of reflection-impulsivity. However, the instrument has several deficiencies, including images designed for school-age children in the USA during the 1960’s. Most importantly, an adult version of the instrument is currently unavailable and the lack of a single repository for the images raises questions regarding the MFFT’s validity and reliability. We developed a 21st century version of the MFFT using images that are familiar to adults and reside in a freely accessible repository. We conducted two studies examining validity and reliability issues. In Study 1, participants interacting with the MFFT-2021, versus those interacting with the original MFFT20, spent more time on the task, took more time in making their first response, and were more likely to complete the task without errors, even though the average number of errors was higher than the comparison group. The coherence of these results is evidence of convergent validity. Regarding predictive validity, the MFFT-2021 remained a reliable predictor of rational thinking, such that participants who demonstrated more reflection (less impulsivity) tended to avoid rational thinking errors. Also, performance on the MFFT-2021 predicted higher quality judgments in processing job characteristic cues with embedded interactions, a form of configural information processing. We also found evidence of concurrent validity: performance on the MFFT-2021 differed in a predictable manner for participants grouped by their performance on the Cognitive Reflection Test. In Study 2, we tested discriminant validity by comparing participant performance on the MFFT-2021 to their performance on the Information Sampling Task (IST), another behavioral measure of reflection-impulsivity used in studies of psychopharmacological and addiction behaviors. For our participants (undergraduate business students), we found that the MFFT was a stronger predictor of performance on rational thinking tasks, and, contrary to prior studies, our exploratory factor analysis identified separate factors for the MFFT-2021 and the IST, supporting discriminant validity, indicating that these two instruments measure different subtypes of reflection-impulsivity.